2018
DOI: 10.1038/s41416-018-0248-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of diabetes after para-aortic radiation for testicular cancer

Abstract: Background While the risk of diabetes is increased following radiation exposure to the pancreas among childhood cancer survivors, its association among testicular cancer (TC) survivors has not been investigated. Methods Diabetes risk was studied in 2998 1-year TC survivors treated before 50 years of age with orchidectomy with/without radiotherapy between 1976 and 2007. Diabetes incidence was compared with general population rates. Treatment-specific risk of diabetes was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Two of these four studies found that, in the first year of follow‐up since diagnosis, the HRs of T2D development were highest for colorectal cancer patients, at 1.53, 16 and 1.47 (95% CI: 1.35–1.60) overall for patients with cancer 13 . Groot and colleagues reported the long‐term incidence rate of T2D at 20 and 30 years after testicular cancer treatment and found that the longer cancer survivors live, the higher the incidence of T2D 20 . Lipscombe and colleagues found the similar pattern that displays the increase in cumulative incidence over time in patients with breast cancer 15 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two of these four studies found that, in the first year of follow‐up since diagnosis, the HRs of T2D development were highest for colorectal cancer patients, at 1.53, 16 and 1.47 (95% CI: 1.35–1.60) overall for patients with cancer 13 . Groot and colleagues reported the long‐term incidence rate of T2D at 20 and 30 years after testicular cancer treatment and found that the longer cancer survivors live, the higher the incidence of T2D 20 . Lipscombe and colleagues found the similar pattern that displays the increase in cumulative incidence over time in patients with breast cancer 15 …”
Section: Resultsmentioning
confidence: 99%
“…Multiple comorbidities, such as hypercholesterolemia, 20 hypertension, 14,16,20,25 cardiovascular disease, 14‐16,19,25,27 dyslipidemia, 14,27 dementia, liver disease, renal disease, rheumatologic disease, peptic ulcer disease, HIV/AIDS, 12,15,27 weight loss, 25 depression, 14 and chronic kidney disease, 12,14,15 at diagnosis were considered. Those with new onset of T2D were more likely to have at least one chronic disease 16 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Jensen et al ( 58 ) also reported a 29% increased risk of diabetes in AYAs compared with the general population and found that diabetes was one of the leading reasons for hospital visits. Studies in specific AYA cancers have also reported increased diabetes risk among HL ( 63 ) and testicular cancer survivors treated with para-aortic RT ( 64 ). The pathogenesis of diabetes in these populations is largely related to pancreatic and adipose tissue toxicity from abdominal RT and chemotherapy, leading to changes in pancreatic function and insulin resistance ( 65-67 ).…”
Section: Priorities For Late Effects Screening and Care In Ayasmentioning
confidence: 99%